Broadly neutralizing monoclonal antibodies for HIV prevention. (21st November 2021) - Miner, Maurine D.; Corey, Lawrence; Montefiori, David
Abstract: Introduction: The last 12 years have seen remarkable progress in the isolation and characterization of at least five different epitope classes of HIV‐specific broadly neutralizing antibodies (bnAbs). Detailed analyses of these bnAb lineages, maturation pathways and epitopes have created new opportunities for vaccine development. In addition, interest exists in passive administration of monoclonal antibodies as a viable option for HIV prevention. Discussion: Recently, two antibody‐mediated prevention (AMP) trials of a passively administered monoclonal antibody targeting the HIV envelope CD4 binding site, called VRC01, provided proof‐of‐concept that monoclonal antibody infusion could offer protection against HIV acquisition. While the trials failed to show overall protection against HIV acquisition, sub‐analyses revealed that VRC01 infusion provided a 75% prevention efficacy against HIV strains that were susceptible to the antibody. The study also demonstrated that in vitro neutralizing activity, measured by the TZM‐bl/pseudovirus assay, was able to predict HIV prevention efficacy in humans. In addition, the AMP trials defined a threshold protective concentration, or neutralization titer, for the VRC01 class of bnAbs, explaining the observed low overall efficacy and serving as a benchmark for the clinical testing of new bnAbs, bnAb cocktails and neutralizing antibody‐inducing vaccines. Newer bnAbs that exhibit greater potency and breadth of neutralization in vitro than VRC01 are available for clinical testing. Combinations of best‐in‐class bnAbs with complementary magnitude, breadth and extent of complete neutralization are predicted to far exceed the prevention efficacy of VRC01. Some engineered bi‐ and trispecific mAbs exhibit similar desirable neutralizing activity and afford advantages for manufacturing and delivery. Modifications that prolong the serum half‐life and improve genital tissue persistence offer additional advantages. Conclusions: Iterative phase 1 trials are acquiring safety and pharmacokinetic data on dual and triple bnAbs and bi‐ and trispecific antibodies in preparation for future AMP studies that seek to translate findings from the VRC01 efficacy trials and achieve acceptable levels of overall prevention efficacy.